Grundfragen der Lyrikologie 1. Lyrisches Ich, Textsubjekt, Sprecher? - Zymner, Rüdiger (Lyrikologie, 2019)
In the German speaking world, questions concerning the voice or speaker of lyrical poems are often oversimplified through recourse to the disputed concept of "the lyrical I." This volume addresses questions surrounding the expressive agent in lyric poems and thus contributes to the controversial debate about adequate forms for conceptualizing lyric poetry at the intersection between philological traditions and practices specific to lyric poetry.